The Role of Moral Reasoning on the Effects of Incentive Schemes and Working Relationships on Whistleblowing: An Audit Experimental Study - Supriyadi Supriyadi; Nidaul Uswah Prasetyaningsih (Gadjah Mada International Journal of Business, 2021)
This study examines the role of moral reasoning in strengthening the working relationship and incentive schemes on the likelihood of reporting accounting fraud. This study predicts that higher moral reasoning or being exposed to incentive schemes are more likely to cause someone to be a whistleblower. However, individuals with a close working relationship with wrongdoers will exhibit a lower propensity to blow the whistle than those with no close working relationship. Finally, moral reasoning is expected to interact with working relationships and incentive schemes to affect the propensity to blow the whistle. Based on a lab-experiment with 147 participants, this study documents that the simple effect of moral reasoning, the working relationship, or an incentive scheme is (marginally) significant. Similarly, the combination of moral reasoning and the working relationship significantly improves the tendency to blow the whistle. However, the combined effects of moral reasoning vs. the working relationship and moral reasoning vs. the working relationship vs. incentive scheme are not significant. This paper confirms previous studies which found that moral reasoning significantly alters the whistleblowing intention but that the impact of moral reasoning is not robust for incentive schemes and working relationships. Some limitations should be considered, namely the textual scenarios of the experimental design, working experiences, and the omission of personal orientation and the personal cost of reporting.